PROFIT ANALYSIS OF BROILER CHICKENS (Gallus Domesticus) FROM THE USE OF SEVERAL PLANT HORMONES - Sembiring, Juna Jakaria; Media Agus Kurniawan; Meriksa Sembiring (Bajang Institute, 2024)
The purpose of this study was to determine the effect of plant hormones on property in raising broiler chickens (Gallus domesticus) and to determine the cost efficiency in the use of different plant hormones for broiler chicken This study used a non-factorial Complete Randomized Design (RAL) with 5 treatments and 4 repeats. The treatments tested were: Ho (control) without hormones, H1 (Neobro), H2 (banana weevil), H3 (bean sprouts), and H4 (sweet potato shoots). Hormone testing is taken from plants by adding EM4 bioactivators and differentiated sugar drops (molasses) for 1 week except for hormones from bean sprouts. The parameters observed are production cost, total revenue, profit/loss analysis, R/C ratio analysis, and Income Over Feed Cost (IOFC). From the results of research that has been done, it is obtained that the use of hormones from several plant hormones